1946
DOI: 10.1051/parasite/1946211025
|View full text |Cite
|
Sign up to set email alerts
|

Sur un distome du genre tamerlania K. I. Skrjabin 1924 avec un catalogue des trématodes des reins d’oiseaux

Abstract: Par Robert-Ph. DOLLFUS Les Trématodes des reins (et des voies urinaires) des Oiseaux sont encore très peu et très mal connus. Je donne ici un aperçu de l'ensemble de nos connaissances sur ces parasites à l'occasion de la description d'un Tamerlania récolté à Richelieu (Indre-et-Loire).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1950
1950
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Ejsriiont (1931Ejsriiont ( , 1932 studied specimens from the same host and concluded that the genus and species as proposed by Korkhaus were synonymous with Tanaisia fedtschenkoi Skrjabin. The present writcrs are in complete agreement with Cheatum (1938) and Dollfus (1946) in accepting Ejsmont's opinion.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…Ejsriiont (1931Ejsriiont ( , 1932 studied specimens from the same host and concluded that the genus and species as proposed by Korkhaus were synonymous with Tanaisia fedtschenkoi Skrjabin. The present writcrs are in complete agreement with Cheatum (1938) and Dollfus (1946) in accepting Ejsmont's opinion.…”
supporting
confidence: 91%
“…In a like manner the writers agree with Yamaguti (1941) in believing Tamerlania japonica Yamaguti, 1935, to be identical with 7. zarudnyi. Further, the present workers can find no reason for not accepting Dollfus' (1946) declaration of the synonymity of his newly created species, T. gallica, with T. zarudnyi.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations